Genotipificação de isolados de vírus da bronquiteinfecciosa das galinhas em surtos ocorridos na aviculturaindustrial de minas gerais, brasil, de 1972 a 1989. - Jose Sergio de Resende (2003)
One segment of DNA (400 bp) situated at the coding end of the n-terminal region of the gene S2 of fifteen brazilian isolates and eight reference strains of infectious bronchitis virus (IBV) was amplified by RT-PCR (reverse transcriptase - polymerase chain reaction) and analysed by RFLP (restriction fragment length polymorphism). The isolates were obtained from industrial flocks (14 isolated from broilers and one from layers) of the poultry industry (Minas Gerais state)undergoing respiratory disease, nephritis and / or reduced / defective laying, during the period from 1972 to 1989. The profiles of restriction by RFLP analysis of amplicons (400 bp) obtained with nine (BstYI, DdeI, HaeIII, HincII, HinfI, HpaII, MaeIII, PstI e ScaI) or five (BstYI, DdeI, HpaII,PstI e ScaI) restriction enzymes, were compared to results obtained for S2 gene sequences (20 IBV) in the GenBank and submitted to RFLP in the WebGene, in addition to 12 IBV (six japanese isolates) in a similar study in Japan. Out of the 55 IBV examined, using the the threesources of information , e. g., RFLP of local, reference and GenBank IBV, the homologous IBV were excluded and 46 were employed for genotyping. Phylogenetic trees with or without root were built using TREECON software and the fifteen brazilian isolates were grouped each into one of three genotypes. The Massachusetts genotype included the reference strains of that serotype and most (nine) of brazilian isolates. The other two genotypes included six isolates considered variants by this study: 283, 290, 297 e 351, G e TII. A greatest occurrence forgenotype Massachusetts might be attributed to the use of this serotype for live vaccines in brazilian poultry industry.